DESIGN PROTOTYPE OF SMART DETECTOR ENVIRONMENT SYSTEM ON SEMICONDUCTOR DETECTOR STORAGE (HPGE) - Rindi Wulandari (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2022)
The HPGe detector is a device that should be cooled when used and can be operated at room temperature. For this reason, it is necessary to monitor the temperature and humidity in the HPGe detector storage area to produce optimal performance. This research was focused on designing a Smart Detector Environment System as a means of monitoring and automatic control of temperature and humidity in the HPGe detector storage. Temperature and humidity detection in the system was carried out by the DHT22 sensor connected to Arduino Uno and the motor driver module. Arduino uno gave the command